Analysis of electromyographic difference between concentric and eccentric phases during seated triceps extension - Chang, Y. W.; Huang, C. Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Seated triceps extension is one of the most common exercises in muscle strengthening and can lead to significant improvement in triceps strength. Seated triceps extension consists of concentric (ascending) and eccentric (descending) phases. Therefore, the purpose of this study was to investigate the difference of electromyography (EMG) in triceps brachii and biceps brachii between concentric and eccentric phases during seated triceps extension.